ESTIMATION OF AGRICULTURE SAVE GARUT CHIPS WITH ACCELERATED TEST METHOD - Ichda Chayati (Jurnal Penelitian Saintek, 2004)
ion  of  shelf  life  0/ arrowroot   chips   by  accelerated    test  was~'I1Ialea,      Arrowroot   chips from   KKPA  was fried, packed,   and  kept  at and  -IO"C and  room  temperature.   followed    by  hedonic   lest  and..,...snemtcut  analysis.   Chemical   compositions    of  arrowroot   chips  were4.97 % moisture,   ]05    % ash.].:/7     % protein,    ]715  % fat,   62.7 %(by   difference)     and    -I.M  %   crude   fiber    content.' Arrowroot   chips fried   with  good   quality  frying    oil  and  packed   with plastic   05 has  /5  weeks  shelflife     bv  estimation   If it is kept  at room